Desain Pembelajaran PAI Realistik di Sekolah Dasar Inklusi Berbasis ICT (Suatu Design Research dalam Pembelajaran Pendidikan Agama Islam SD Inklusi di Kabupaten Jombang) - Jasminto (Menara Tebuireng, 2016)
Innovation of Learning PAI in SD Inclusion is indispensable in the midst of learning patterns PAI, it is still centered on the non-inclusion SD. People are still paying less attention to the existence of SD Inclusion as one entrusted primary school children with special needs, particularly in the districts of Jombang. It underlies researchers design learning model PAI Realistic ICT-based learning (PPR). The specific objective of this study was to produce a prototype design of PPR, and see the effectiveness of their application in teaching in elementary PAI Inclusion Jombang. While the long-term goal of this research is the result of the design of PPR model design can be used as an enrichment of teaching materials and can be used as a foundation for enhancing the quality of learning PAI SD Inclusion. The method used is Design Research which each cycle consisting of the stages of preparation for the experiment (preparatory studies), design experiment (the implementation of the design of experiments) and retrospective analysis (analysis of data obtained from the previous stage). The study was conducted in three elementary Inclusion Jombang. Steps taken at the stage of preparation for the experiment (preparatory studies) is the study of literature, discussions with teachers, designing learning model Realistic SD PAI Inclusion ICT and initial design study. While at the design stage of the experiment (the implementation of the experimental design) data collection and testing in 3 SD Inclusion Jombang. The results of this study indicate that the model PPR can stimulate and improve students' understanding of concepts as well as to foster a love of students towards subjects PAI. Learning implementation went smoothly, the response of students and teachers is very good